Pond dyke utilization: An innovative means for enhancing productivity and income under Integrated Farming System in North East Hill Region of India - BABU, SUBHASH; DAS, ANUP; MOHAPATRA, K P; YADAV, G S; SINGH, RAGHAVENDRA; TAHASHILDAR, MOUTUSI; DEVI, M THOITHOI; DAS, SAMIR; PANWAR, A S; PRAKASH, N (The Indian Journal of Agricultural Sciences, 2019)
Integrated farming system (IFS) is a sustainable and effective means for improving rural economy due to its cumulative cost effectiveness, low investment and higher profitability. IFS has greater role for livelihood improvement in north eastern region (NER) of India where most of the farmers are small and marginal. Farm pond for multiple uses is the integral part of IFS system in the region. In a typical farm pond, about 40-60% area is given to dyke, which is generally very productive area due to water and organic matter availability in the vicinity. In-spite of its high production potential, pond dykes are seldom effectively utilized. Fish pond dyke intensification with crops and poultry an play a significant role in increasing manifold production, income, nutrition and employment opportunities of rural populations. In present study, three different components like fish, poultry and sequential vegetables production were employed in at ICAR Research Complex for NEH Region, Umiam, Meghalaya (980 amsl). The results indicated that in integrated pond management, two additional enterprises, viz. poultry and year round vegetable cultivation exhibited production and income enhanced over traditional practice. Integration of fish-poultry and year round vegetable production recorded 750% higher system production efficiency and 858.6% higher average profitability over the traditional practice. Furthermore, pond dyke intensification and poultry production also recorded 600% higher employment generation over non-integration. The utilization of family labour round the year in pond based integrated production system increases the production as well as employment opportunities for income generation. The overall results revealed that the integrated pond management with poultry, fish and vegetables on pond dyke is an excellent approach for sustainable production as well as income and employment generation for the resource poor rural households.